1986
DOI: 10.1056/nejm198610023151404
|View full text |Cite
|
Sign up to set email alerts
|

Outcome in Patients with Asymptomatic Neck Bruits

Abstract: Five hundred asymptomatic patients with cervical bruits were followed prospectively by clinical and Doppler examination for up to four years (mean, 23.2 months) to identify the variables predicting outcome. Thirty-six patients had strokes or transient ischemic attacks, 51 had cardiac ischemic events, and 45 died. At one year the incidence of cerebral ischemic events (transient ischemic attacks and strokes) was 6 percent, that of cardiac ischemic events was 7 percent, and that of death was 4 percent. The overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
170
3
10

Year Published

1989
1989
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 533 publications
(191 citation statements)
references
References 21 publications
8
170
3
10
Order By: Relevance
“…25 In addition, patients with carotid artery disease more often die from coronary atherosclerosis than from complications of carotid atherosclerosis. 26 ' 27 Thus, the relation of measurements of carotid atherosclerosis to the extent of disease in the coronary circulation may be more important than its use in measuring local disease.…”
Section: Resultsmentioning
confidence: 99%
“…25 In addition, patients with carotid artery disease more often die from coronary atherosclerosis than from complications of carotid atherosclerosis. 26 ' 27 Thus, the relation of measurements of carotid atherosclerosis to the extent of disease in the coronary circulation may be more important than its use in measuring local disease.…”
Section: Resultsmentioning
confidence: 99%
“…As with asymptomatic carotid bruit, an asymptomatic stenosis of the carotid artery is an important indicator of concomitant ischemic cardiac disease. 68,69,72 There have been 4 published randomized controlled trials that were designed to address the benefit of carotid endarterectomy in patients with asymptomatic carotid artery stenosis. The CASANOVA (Carotid Artery Stenosis with Asymptomatic Narrowing: Operation Versus Aspirin) study was inconclusive.…”
Section: Asymptomatic Carotid Stenosismentioning
confidence: 99%
“…46 In the Toronto prospective study of carotid bruit 44 and stenosis, 47 both bruit and degree of stenosis indicated higher cardiovascular risk.…”
Section: Asymptomatic Chd In Patients With Atherosclerotic Carotid Stmentioning
confidence: 99%